Reaction pathways and transition states of the C-C and C-H bond cleavage in the aromatic pyrene molecule - A Density Functional study - Al-Yassiri, Muntadar Abd Al-Barri Hussain; Shanshal, Muthana (European Journal of Chemistry, 2015)
The activation and reaction energies of the C-C and C-H bonds cleavage in pyrene molecule are calculated applying the Density Functional Theory and 6-311G Gaussian basis. Different values for the energies result for the different bonds, depending on the location of the bond and the structure of the corresponding transition states. The C-C bond cleavage reactions include H atom migration, in many cases, leading to the formation of CH2 groups and H-C≡C- acetylenic fragments. The activation energy values of the C-C reactions are greater than 190.00 kcal/mol for all bonds, those for the C-H bonds are greater than 160.00 kcal/mol. The reaction energy values for the C-C bonds range between 56.497 to 191.503 kcal/mol. As for the C-H cleavage reactions the activation energies range from 163.535 to 165.116 kcal/mol, the reaction energies are nearly constant, 117.500kcal/mol. The geometries of the transition states and reaction products are discussed too.